The Influence of Dhikr on Anxiety in Acute Coronary Syndrome (ACS) Patients at Dr. Chasbullah Abdulmadjid Hospital, Bekasi City - Sulistiyowati, Heppy; Jumaiyah, Wati; Purnamawati, Dewi; Sofiani, Yani; Susanto, Budi; Prima, Ashar; Hamdah, Hamdah (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: This study was to determine the effect of dhikr on anxiety in ACS patients at Dr. Chasbullah Abdulmadjid General Hospital, Bekasi City. Methods: The research method used pre- and post-quasy experiments in the control group and the intervention group. This study used the HARS questionnaire and family support for 76 respondents. Result: Data analysis using multiple logistic regression tests The results showed that the proportion in the control group with mild-moderate anxiety was 31.6% and severe anxiety was 18.4%; the proportion in the intervention group with mild-moderate anxiety was 46.1% and severe anxiety was 3.9%. Dhikr (p = 0.006) and history of heart disease (p = 0.023) significantly influence anxiety after being controlled by age (p = 0.244) (p = 0.001 omnimbus). The dominant factor that influences anxiety is dhikr (OR 10.674).  Conclusions : Dhikr is an act of remembering Allah that can be used to reduce anxiety in SKA patients. This can be done independently by reading istigfar, tasbih, hauqalah, and takbir for 15 minutes in the morning and evening. Therefore, nursing services using dhikr as an effort to reduce anxiety in ACS patients.